2018
DOI: 10.1080/02786826.2018.1490005
|View full text |Cite
|
Sign up to set email alerts
|

Size resolved chemical composition of nanoparticles from reactions of sulfuric acid with ammonia and dimethylamine

Abstract: Nanoparticle formation and growth driven by acid-base chemistry was investigated by introducing gas-phase sulfuric acid (H 2 SO 4 ) with ammonia (NH 3 ) or dimethylamine (DMA) into a flow tube reactor. A thermal desorption chemical Ionization mass spectrometer was used to measure the sizeresolved chemical composition of H 2 SO 4 -DMA and H 2 SO 4 -NH 3 nanoparticles formed under dry conditions and at 60% relative humidity. In contrast with predictions for bulk aqueous systems, nanoparticles showed a strong siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 94 publications
5
41
0
Order By: Relevance
“…Comparison between measured and modeled growth rates at small diameters (2 nm) in the acid-base system (sulfuric acid-dimethylamine and sulfuric acid-ammonia) indicates that water has no significant effect on particle growth . The same can be concluded for the sulfuric acid-ammonia system at larger diameters (∼ 10 nm; see Chen et al, 2018).…”
Section: Uncertainties and Limitations Of Santiagosupporting
confidence: 70%
See 1 more Smart Citation
“…Comparison between measured and modeled growth rates at small diameters (2 nm) in the acid-base system (sulfuric acid-dimethylamine and sulfuric acid-ammonia) indicates that water has no significant effect on particle growth . The same can be concluded for the sulfuric acid-ammonia system at larger diameters (∼ 10 nm; see Chen et al, 2018).…”
Section: Uncertainties and Limitations Of Santiagosupporting
confidence: 70%
“…However, the involvement of ammonia in the formation of new particles at the relatively warm conditions close to the surface is not clear yet. A recent study indicates that ion-induced ternary nucleation can explain some new particle formation events in the boreal forest in Finland ; evidence that NH 3 is important in polluted boundary layer environments has been presented earlier (Chen et al, 2012). Most recently, Jokinen et al (2018) showed that ion-induced ternary nucleation is important in coastal Antarctica.…”
mentioning
confidence: 92%
“…The concentration of HNO 3 vapor was estimated by assuming that it achieves its saturation vapor pressure prior to exiting the saturator. The inlet for this study was altered from the Chen et al study 23 by the addition of a movable, 1/8" OD stainless steel tube inserted into the inlet end of the flow tube ( Figure 1). The stainless-steel tube was capped, and the gaseous nitric acid containing N 2 entered the flow tube through slits cut out of the cap to promote mixing.…”
Section: ■ Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Recently, however, several studies have reported that particles composed of sulfuric acid and base have been observed to be more acidic in particle diameters smaller than 15 nm, 21,22 and in the specific case of H 2 SO 4 -DMA particles, they even become more basic under dry conditions at some sizes. 23 This disparity between the composition of clusters and nanoparticles in such acid−base systems warrants additional investigation. These prior studies examined trends in nanoparticle composition from reactions of bases with sulfuric acid, a low-volatility diprotic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…38 Finally, particle-bound amines (aminium and ammonium ions) have been detected using thermal desorption chemical ionization mass spectrometry (TDCIMS), where the particles are collected onto the tip of a platinum wire followed by subsequent thermal desorption and ionization using water clusters formed using a 210 Po radioactive source. 12,39,40 Ambient ionization mass spectrometry methods have been exponentially growing over the past ten years due to their versatility, ease of use, reduced fragmentation due to 'soft' ionization mechanisms, and minimal sample preparation. 41 We report here studies of the use of NMP as a somewhat unconventional ambient ionization agent for ammonia and a series of amines.…”
Section: Introductionmentioning
confidence: 99%